2004
DOI: 10.1177/0265407504042834
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Offline and Online Friendship Qualities at Different Stages of Relationship Development

Abstract: The present study was designed to compare offline and online friendship qualities at different stages of relationship development. The sample consisted of 162 Hong Kong Internet users. They were asked to think of two friends, one they knew through face-to-face interactions and one they knew through the Internet, and then describe the qualities of their offline and online friendships. Results revealed that offline friendships involved more interdependence, breadth, depth, code change, understanding, commitment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(107 citation statements)
references
References 17 publications
2
97
1
7
Order By: Relevance
“…We know from previous research that cross-sex friendships are less common offline than same-sex friendships, forming as little as 20% of adult friendships (Kalmijn's, 2002). Cross-sex friendships may be more likely to occur online (Parks & Roberts 1998) and be closer and more developed than same-sex online friendships when they do (Chan & Cheng 2004). Age homophily is powerful offline, "stronger than any other dimension" (McPherson et al 2001, p. 424) in close friendship.…”
Section: Homophily In Online Friendshipsmentioning
confidence: 98%
See 1 more Smart Citation
“…We know from previous research that cross-sex friendships are less common offline than same-sex friendships, forming as little as 20% of adult friendships (Kalmijn's, 2002). Cross-sex friendships may be more likely to occur online (Parks & Roberts 1998) and be closer and more developed than same-sex online friendships when they do (Chan & Cheng 2004). Age homophily is powerful offline, "stronger than any other dimension" (McPherson et al 2001, p. 424) in close friendship.…”
Section: Homophily In Online Friendshipsmentioning
confidence: 98%
“…Chan and Cheng's (2004) version of Parks and Roberts' (1998) 18-item instrument assessed relational development. Previous research demonstrates that the scale assesses several manifestations of relational development such as "the feeling of mutual dependence," "the variety of conversational topics shared," and "the degree of self-disclosure" (Chan and Cheng 2004, p. 310).…”
Section: Relational Developmentmentioning
confidence: 99%
“…In traditional face-to-face interpersonal relationships, a popular belief is that cross-sex friendships are harder to develop because of the restrictions of both structural factors (such as the lack of opportunities for both sexes to meet and to interact continuously) and normal factors (such as the social disapproval if married people cultivate cross-sex relationships) (Chan & Cheng, 2004). After reviewing relevant literature, which indicated that both structural and normal factors were limited in online settings, Chan, Cheng and their associates (Chan & Cheng, 2004;Cheng, Chang, &Tong, 2006) conducted two waves of studies on associations between online and offline friendship qualities and gender compositions.…”
Section: Network Heterogeneitymentioning
confidence: 99%
“…After reviewing relevant literature, which indicated that both structural and normal factors were limited in online settings, Chan, Cheng and their associates (Chan & Cheng, 2004;Cheng, Chang, &Tong, 2006) conducted two waves of studies on associations between online and offline friendship qualities and gender compositions. They found that in online settings, qualities of cross-sex friendship were generally higher than those of same-sex friendship.…”
Section: Network Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation